(untitled) (Journal of Student Affairs in Africa, 2021)
Reviewed by Vicki TrowlerIn my day job as a researcher of higher education, one of the topics I have studied and written about is student engagement. Engagement of, and by, students is now universally held to be central to student success (Trowler, 2010) and all of us working in this arena grapple with ways to facilitate this. Kahu and Nelson (2018) argue that an alignment of institutional and student factors unlocks student engagement, and thus learning. Specifically, when the curriculum is aligned with students’ interests, experiences and ’future selves’, students will engage on an emotional level, so learning can take place. Preparing slides ahead of an undergraduate lecture, I sit staring at my computer screen, wondering asdoes every other lecturer preparing to teach, how best to make the material engaging, accessible, relevant. How do we best speak to not just the students’ past, current and ’future selves’, but also their possible selves, subverting the predictions of ’differential outcomes’ that doom students from certain backgrounds (categorised by "race", ethnicity, gender,social class, disability status, geography and the other cleavages to which inequality clings persistently) to lesser attainment?